THE MEANING OF TOR-TOR SOMBAH SYMBOL IN THE DEATH CEREMONY OF SAUR MATUA ETHNIC BATAK - Syahputri, Dinda Nabilla; Marsa, Yummy Jumiati (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2025)
The research entitled “The Symbolic Meaning of Tor-Tor Sombah in the Saur Matua Death Ceremony of the Simalungun Batak Ethnic” discusses dance art related to the implementation of the Sayur Matua traditional death ceremony. This research aims to explore the symbolic meaning contained in the Tor-Tor Sombah dance and analyze its relationship with the traditional ritual process of the Simalungun Batak community. In addition, this research also seeks to describe the performance form of Tor-Tor Sombah in the series of traditional ceremonies. One of the focuses of this research is to preserve the cultural heritage of the ancestors so that it is maintained and not forgotten, so that the next generation, especially children and grandchildren, can understand and respect the values and messages contained in the Batak Simalungun tradition. The method used in this research is a qualitative approach with phenomenology. The results revealed that Tor-Tor Sombah has a very significant role in the Sayur Matua death ceremony for the Simalungun Batak community.